EFFECT OF LOW INTENSITY CLOSED KINEMATIC CHAIN EXERCISE WITH PULMONARY REHABILITATION IN COPD - Patil, Chandrakant; Patil, Smita (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: COPD is a preventable and treatable disease with progressive airway restriction. There is reduced physical activity in COPD, and it is also associated with reduced peripheral and respiratory muscle weakness; hence, the present study is conducted with the aim to determine the effect of low-intensity closed kinematic chain exercise along with pulmonary rehabilitation in COPD. Materials and Methods: A randomized controlled trial was carried out on 22 samples with COPD. The individuals were selected based on inclusion and exclusion criteria and were divided into 2 groups. Group A was treated with low-intensity CKC exercise along with pulmonary rehabilitation, and Group B was treated with only a pulmonary rehabilitation program. The study place was OPD Krishna College of Physiotherapy, Karad. The protocol was given for 6 weeks (3 times per week). The outcome measures were the 6-minute walk test, the time up and go test for balance, and maximal voluntary contraction. Result: There was statistically significant improvement in group A as compared to group B. The six-minute walk test distance was significantly improved in group A as compared to group B (p=0.0256). The balance was improved in group A as compared to group B (p=0.0069). Conclusion: The study concluded that the Low intensity closed kinetic exercises should also be implemented in routine pulmonary rehabilitation for better functional outcome in individuals with COPD